Eco-efficiency, environmental and sustainable innovation in recycling energy and their effect on business performance: evidence from European SMEs - Majid, Sara; Zhang, Xin; Khaskheli, Muhammad Bilawal; Hong, Feng; King, Patricia Jie Hung; Shamsi, Imran Haider (Multidisciplinary Digital Publishing Institute, 2023)
This paper examines the influence of adopting resource efficiency actions, saving water, saving energy, using renewable energy, saving materials, minimizing waste, selling scrap, recycling, using durable products, promoting environmental responsibility, and offering green marketing products and services on the performance of small and medium-sized enterprises (SMEs). More specifically, we investigate specific resource efficiency actions and their impact on production costs, investment, the available support for product expansion, and the effect of encountered barriers on SME performance. We develop a theoretical framework based on stakeholder- and resource-based theories to serve as the foundation for this analysis. We use these theories to explain the link between eco-efficiency actions, firm performance, and ecological behavior, along with public policy and innovation. This study uses Flash Eurobarometer survey datasets FL342, FL381, FL426, and FL456, which cover SMEs across time and sectors in 28 EU countries. The data are analyzed through descriptive and ordered logit regression analysis, using the Statistical Package for the Social Sciences (SPSS) to test the relationship between the above variables and the parameters. In terms of practical implications, these findings are crucial in helping SMEs pursue sustainable development. According to the findings, SMEs lack information on how implementing eco-efficiency action affects their financial health and sustainable innovation. This study can provide valuable insights into how implementing eco-efficiency practices can positively impact a companys bottom line, good health, and employees well-being and how SMEs can use this information to make more informed decisions. Additionally, the findings can help inform policy makers about how to better support SMEs in pursuing sustainable development.